FAO PRESS RELEASE “FAO DIRECTOR-GENERAL GRAZIANO DA SILVA HANDS OVER HELM TO QU DONGYU WITH CALL TO IMPROVE ACCESS TO QUALITY FOOD FOR ALL” - Article Editorial (Ветеринария сегодня)
FAO press release “FAO director-general graziano da silva hands over helm to qu dongyu with call to improve access to quality food for all”.